Gold nanoparticle trapping and delivery for therapeutic applications - Aziz, MS (Dove Medical Press, 2012)
A new optical trapping design to transport gold nanoparticles using a PANDA ring resonator system is proposed. Intense optical fields in the form of dark solitons controlled by Gaussian pulses are used to trap and transport nanoscopic volumes of matter to the desired destination via an optical waveguide. Theoretically, the gradient and scattering forces are responsible for this trapping phenomenon, where in practice such systems can be fabricated and a thin-film device formed on the specific artificial medical materials, for instance, an artificial bone. The dynamic behavior of the tweezers can be tuned by controlling the optical pulse input power and parameters of the ring resonator system. Different trap sizes can be generated to trap different gold nanoparticles sizes, which is useful for gold nanoparticle therapy. In this paper, we have shown the utility of gold nanoparticle trapping and delivery for therapy, which may be useful for cosmetic therapy and related applications.